Left auditory cortex is involved in pairwise comparisons of the direction of frequency modulated tones - Angenstein, Nicole; Brechmann, André (Frontiers in Neuroscience, 2013)
Evaluating series of complex sounds like those in speech and music requires sequential comparisons to extract task-relevant relations between subsequent sounds. With the present functional magnetic resonance imaging (fMRI) study, we investigated whether sequential comparison of a specific acoustic feature within pairs of tones leads to a change in lateralized processing in the auditory cortex of humans. For this we used the active categorization of the direction (up versus down) of slow frequency modulated (FM) tones. Several studies suggest that this task is mainly processed in the right auditory cortex. These studies, however, tested only the categorization of the FM direction of each individual tone. In the present study we ask the question whether the right lateralized processing changes when, in addition, the FM direction is compared within pairs of successive tones. For this we use an experimental approach involving contralateral noise presentation in order to explore the contributions made by the left and right auditory cortex in the completion of the auditory task. This method has already been applied to confirm the right-lateralized processing of the FM direction of individual tones. In the present study, the subjects were required to perform, in addition, a sequential comparison of the FM-direction in pairs of tones. The results suggest a division of labor between the two hemispheres such that the FM direction of each individual tone is mainly processed in the right auditory cortex whereas the sequential comparison of this feature between tones in a pair is probably performed in the left auditory cortex.